Iodized salt at households and retail shops in a rural community of Northern India - Srivastava, Rahul; Yadav, Kapil; Upadhyay, Ravi P; Silan, Vijay; Sinha, Smita; Pandav, Chandrakant S; Karmarkar, Madhu G (South East Asia Journal of Public Health, 2013)
Iodine is an essential micronutrient for humans but its deficiency can cause public health problems. The objective of this study was to estimate the consumption of adequately iodized salt on a household level, and to study the availability, procurement, storage, cost, and knowledge regarding iodized salt and iodine deficiency disorders amongst retail shopkeepers from the Ballabgarh block of Haryana in Northern India. This rural area was the location used for a community-based cross-sectional study by simple random sampling. Salt samples were collected from 363 selected households (out of the calculated 400 household samples) and all the retail shops (233) in the study area. Salt was tested using an iodometric titration method at the Indian Coalition for Control of Iodine Deficiency Disorders (ICCIDD) laboratory in New Delhi. Retail shopkeepers were also interviewed regarding their knowledge and practices. Adequately iodized salt (?15 parts per million) was consumed in 65.2% of the households, while 17.3%, of the residents were consuming salt with no iodine added (0-5ppm). Adequately iodized salt was sold by 76.3% of the retail establishments, while 12.3% were selling salt without any added iodine (0-5ppm). About 84% of the shopkeepers were aware that they are selling iodized salt. It was reported by 94% of the retail shopkeepers that iodized salt is necessary for good health but none of them could identify all the iodine deficiency disorders. Effective strategies are required to educate both consumers and suppliers to achieve Universal Salt Iodization at household level. South East Asia J Public Health | Jan-June 2012 | Vol 2 Issue 1 | 18-23 DOI: http://dx.doi.org/10.3329/seajph.v2i1.15256